Dynamic volatile organic compound fingerprinting of apple fruit during processing. Issue 1 (September 2015) - Farneti, Brian; Khomenko, Iuliia; Cappellin, Luca; Ting, Valentina; Costa, Guglielmo; Biasioli, Franco; Costa, Fabrizio
Abstract The aroma profile in apple was investigated during artificial processing operated with a device imitating the human consumption. The system, composed by a "chewing device" coupled with a Proton Transfer Reaction – Time of Flight-Mass Spectrometry (PTR-ToF-MS), allowed an accurate dynamic volatile organic compound (VOC) fingerprinting suitable to study the volatile kinetics of three apple cultivars ('Golden Delicious', 'Fuji', and 'Granny Smith') during shelf-life ripening. The obtained results demonstrate the complementarity between the dynamic VOC assessment during "mastication" and the usual static headspace analysis. The great advantage of such analytical approach was the possibility to study the kinetics of the volatiles released during eating and the possibility to consider their concentration similar to in vivo condition resulting to an improved characterization of the aroma profile. Moreover, differences in textural properties of apple flesh revealed a possible direct role of the cell wall architectural structure in the regulation of VOC release during consumption. This strategy may be ideal for VOC assessment addressed to investigate fruit quality aspects impacting the consumer appreciation.